V.i.7. Items concerning John Pitt Kennedy's military/eingineering career and public appointments, - Kennedy, John Pitt, 1796-1879 (1849)
MS 49,529 /81 Folder 1 : Documents concerning John Pitt Kennedy's military appointments and leave of absense. Also includes his appointment as Commissioner of the Peace for Co. Limerick. Covers 1849-1853. [9 items.]